2011
DOI: 10.1016/j.bspc.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Examination of time-varying kinematic responses to support surface disturbances

Abstract: Abstract:To examine the evolution of inter-segmental coordination over time, a previously developed multi-variate model of postural coordination during quiet stance (Kuo et al. 1998) has been extended. In the original model, postural coordination was treated as an eigenvalue-eigenvector problem between two segmental degrees of freedom represented by angular displacements of the trunk and lower limb. Strategies of postural coordination were then identified using the sign of the covariance between the two segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Time-frequency analysis of centre of pressure motion during unperturbed stance has revealed that human balance is non-stationary with time-varying properties [ 15 , 16 ]. Gurses et al [ 17 ] examined the evolution of intersegmental coordination over time, adapting the model of Kuo et al [ 18 ] by dividing trials into overlapping time segments of 16 s duration. Results indicated statistical and spectral characteristics across the entire trial can differ from individual time segments of the same trial displaying time-varying intersegmental coordination behaviours [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-frequency analysis of centre of pressure motion during unperturbed stance has revealed that human balance is non-stationary with time-varying properties [ 15 , 16 ]. Gurses et al [ 17 ] examined the evolution of intersegmental coordination over time, adapting the model of Kuo et al [ 18 ] by dividing trials into overlapping time segments of 16 s duration. Results indicated statistical and spectral characteristics across the entire trial can differ from individual time segments of the same trial displaying time-varying intersegmental coordination behaviours [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gurses et al [ 17 ] examined the evolution of intersegmental coordination over time, adapting the model of Kuo et al [ 18 ] by dividing trials into overlapping time segments of 16 s duration. Results indicated statistical and spectral characteristics across the entire trial can differ from individual time segments of the same trial displaying time-varying intersegmental coordination behaviours [ 17 ]. Employing stationary-based data analysis techniques to non-stationary balance or coordination data will result in misrepresentations of the full temporal characteristics of postural control.…”
Section: Introductionmentioning
confidence: 99%
“…This might explain the heightened ankle strategy use in longer delays, reflecting Versteeg et al's findings. In a 2011 study by Gurses et al [63], the authors compared balance strategies of young adults vs elderly for different frequencies of perturbation and found that young adults predominantly used hip strategy, whereas elderly individuals employed a mix of hip and ankle strategies used by elderly. This implies an age-related shift towards ankle strategy in response to perturbations.…”
Section: Balance Strategiesmentioning
confidence: 99%
“…This might explain the heightened ankle strategy use in longer delays, reflecting Versteeg et al's findings. In a 2011 study by Gurses et al[63], that ankle strategy dominated when perturbance frequency was below 2.11 Hz.…”
mentioning
confidence: 95%
“…Data analyses from CoP signal (basic measurement for estimating human balance in quasi static and dynamic conditions, which is derived from kinetic outputs) is performed at time and frequency domains [17]. Figures 4a and b show exemplar CoP x and CoP y time signals of an healthy subject collected at quiet stance and their related Fast Fouriér Transformations (FFT, see below paragraph for an explanation/ implication of FFT, Figures 4c and d).…”
Section: Case Study (A Healthy Versus Bilateral Vestibular Loss Patient)mentioning
confidence: 99%